Development of Mathflip-Pad E-modules based on PBL and Muhammadiyah values to facilitate student engagement and mathematical communication - Harsono, Tiara Friaesa; Wati, Unik Ambar (Jurnal Penelitian Ilmu Pendidikan, 2025)
Student engagement and mathematical communication are essential 21st-century competencies; however, many students still struggle to actively participate and express mathematical ideas in conventional classrooms. This study aimed to develop a MathFlip-Pad electronic module (e-module) based on Problem-Based Learning (PBL) and Muhammadiyah values and to examine its validity, practicality, and effectiveness in enhancing student engagement and mathematical communication skills. This study employed a Research and Development (R&D) method using the ADDIE model. The e-module was designed as a flipbook-style interactive learning media integrating PBL stages and Islamic values. Validation involved subject matter, media, and pedagogy experts, followed by a limited trial with eighth-grade students at a Muhammadiyah junior high school. Data was collected through expert validation, response questionnaires, and classroom observation. Expert validation scores for the material and media were 90.63% and 92.2% (highly valid), while student and teacher responses were 89.5% and 90.6% (very good). Observations showed that 92% of students actively participated in discussions, 95% engaged in Polypad exploration, and 87% used appropriate mathematical language. The study concludes that the MathFlip Pad e-module is feasible and effective in enhancing engagement and mathematical communication.